Natural Clostridioides difficile Toxin Immunization in Colonized Infants. (29th June 2019) - Kociolek, Larry K; Espinosa, Robyn O; Gerding, Dale N; Hauser, Alan R; Ozer, Egon A; Budz, Maria; Balaji, Aakash; Chen, Xinhua; Tanz, Robert R; Yalcinkaya, Nazli; Conner, Margaret E; Savidge, Tor; et al.
Abstract: Background: Clostridioides ( Clostridium ) difficile colonization is common among infants. Serological sequelae of infant C. difficile colonization are poorly understood. Methods: In this prospective cohort study of healthy infants, stools serially collected between ages 1-2 and 9-12 months were tested for non-toxigenic and toxigenic C. difficile (TCD). Cultured isolates underwent whole-genome sequencing. Serum collected at 9–12 months underwent measurement of IgA, IgG, and IgM against TCD toxins A and B and neutralizing antibody (NAb) titers against toxin B. For comparison, antitoxin IgG and NAb were measured in cord blood from 50 mothers unrelated to study infants. Results: Among 32 infants, 16 (50%) were colonized with TCD; 12 were first colonized >1 month before serology measurements. A variety of sequence types were identified, and there was evidence of putative in-home (enrolled siblings) and outpatient clinic transmission. Infants first colonized with TCD >1 month prior had significantly greater serum antitoxin IgA and IgG against toxins A ( P = .02 for both) and B ( P = .009 and .008, respectively) compared with non–TCD-colonized infants, and greater IgG compared with unrelated cord blood ( P = .005). Five of 12 (42%) colonized infants had detectable NAb titers compared with zero non–TCD-colonized infants ( P = .02). Breastfeeding was not associated with differences in serological measurements. Conclusions: TCD colonization is associated with a humoral immune response against toxins A and B, with evidence of toxin B neutralization in vitro. The extent and duration of protection against CDI later in life afforded by natural C. difficile immunization events require further investigation. Abstract : Compared with noncolonized infants, infants with toxigenic Clostridioides difficile colonization develop greater levels of Immunoglobin A and Immunoglobin G against toxins A and B and neutralizing antibodies against toxin B, suggesting that infant C. difficile colonization is a natural immunization event.